Migration and growth of population in Assam: nature, and consequences - SARMAH, PAPORI (International Journal of Psychosocial Rehabilitation, 2020)
Two principal movements currently dominate the socio political landscape in Assam. One is the demand for autonomy and statehood by tribal groups headed by the Bodos and push against illegal migrants from Bagaldesh by native people of Assam. Migration is the third component of population change after mortality and fertility. Assam is situated in the north-east of India- bordering seven states and two countries viz. Bangladesh and Bhutan. The flows of immigrants started during the rule of British and continued till today due to the pull and push factor. The large volume of influx of migrants both interstate and international migration have modified the population structure of Assam in respect of ethno-religious composition, occupation structure etc. It adversely affects the social, economic and political environment of Assam, creating law and order problems where immigrants are present in large number. Migration is not a new phenomenon for Assam, but what is new is its massive nature since the beginning of the 20th century. The extent of migration and its impact on population growth and socio-economic condition in Assam has been a matter of controversy especially in the last two three decades. In this paper an attempt has been made to study the nature of migration of Assam and its impact on population growth of Assam with the help of secondary data.